Conductive hearing loss does not affect spatial learning and memory in middle-aged guinea pigs - K. M. Barry; J. C. J. Jimena; H. Y. Tarawneh; W. Johnsen; A. Osmanbasic; J. Rodger; W. H. A. M. Mulders (Scientific Reports)
Abstract Hearing loss (HL) in mid-life has been suggested as a risk factor for cognitive decline. It is unclear whether this relationship is due to deprivation of auditory input alone, degenerative processes, or a combination. Animal models are useful to investigate underlying neural mechanisms as human studies can be confounded by various factors. However, most animal studies use young animals and often exclude females. We used middle-aged guinea pigs of both sexes to investigate whether 8 weeks of auditory deprivation due to conductive HL caused spatial learning and memory impairments. Forty guinea pigs (20 M, 20 F, ~ 12 months) were tested in the Morris Water Maze (MWM) to assess baseline spatial learning and memory. In 20 of these animals (10 M, 10 F) the ear canal was plugged and 8 weeks later, animals were again assessed in MWM. No deficits in spatial learning or memory were observed in either sex. HL caused a small decline in body weight suggesting some stress associated with conductive HL, although adrenal weight, corrected for body weight, did not change. Our data suggest that auditory input deprivation alone does not affect spatial cognition in middle-age, in line with recent human data suggesting that additional risk factors need to be present.